Analysis of Obesity And Axillary Lymph Nodes on Mammography - Aysegul Akdogan Gemici; Ersoy Bayram; Nigar Gultekin; Ercan Inci (Medical Laboratory Technology Journal, 2019)
Fat-infiltrated lymph nodes mostly seen on mammograms (MG) of the elderly and obese women. We analyzed the fat infiltration of lymph nodes for its potential use in estimating body mass index (BMI). 2D digital MG of 157 women assessed by one breast radiologist and one radiology resident. For each patient, the largest lymph node chosen as the index by analyzing the medial, lateral oblique (MLO) views. The width and length of the node and the hilum, the cortex, and the Hilo-cortical ratio (HCR) were measured. Breast density was categorized according to the ACR BI-RADS 4th edition and divided into two groups as dense and non-dense. Obesity was defined as BMI ≥ 30 kg/m2, overweight as BMI